Orthopedic Sports Medicine Principles and Practice - Margheritini, Fabrizio; Rossi, Roberto; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2011)
Aim of this book is to give an update on the main issues in sports traumatology and orthopedics, involving different body sections. Exploring the most important aspects of sports medicine - from anatomy to normal movements description, from diagnosis to sports injuries treatment, from conservative to surgical treatments - it gives a global overview of the field, describing also diagnostic tools recently introduced in this field, such as hip arthroscopy, and taking into consideration related areas like nutrition, prevention, training and rehabilitation. The single chapters deals with relevant problems such as emergencies on the field, pathologies of the upper and lower extremity, spine problems in athletes. Each injury is approached on the basis of both the specific body area and of the different sports/activities. Written by a multidisciplinary team of experts, this volume will be a fundamental book for orthopedic surgeons, physiotherapists, general practitioners, personal and athletic trainers, offering them a useful tool for the management of most frequent injuries in sports medicine.
Keywords: Medicine; Orthopedics; Rehabilitation; Sports medicine; Medicine & Public Health; Orthopedics; Sports Medicine; Rehabilitation